ENHANCING SOLDIERS’ SUSTAINABLE PERFORMANCE THROUGH TRANSFORMATIONAL LEADERSHIP AND COMPENSATION: THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Wisnu Adityara; Dwi Cahyono; Toni Herlambang (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the direct and indirect effects of transformational leadership and compensation on sustainable performance, with Organizational Citizenship Behavior (OCB) as a mediating variable among soldiers of the 509th Infantry Battalion. Using an explanatory research approach, data were collected from 80 soldiers through a structured questionnaire and analyzed using SEM-PLS. The results show that transformational leadership and compensation significantly improve sustainable performance. Both variables also positively influence OCB, which in turn enhances sustainable performance. Mediation testing confirms that OCB partially mediates the effects of transformational leadership and compensation on sustainable performance, indicating that voluntary extra-role behaviors serve as an important behavioral pathway through which leadership and compensation strengthen long-term performance stability. The novelty of this research lies in integrating sustainable performance with leadership, compensation, and OCB within a military context—an area that remains underexplored in previous studies. This study also provides new empirical evidence on how OCB functions as a strategic mediator in high-discipline, high-risk organizational environments. The findings contribute theoretically by reinforcing models of transformational leadership, compensation, OCB, and sustainable performance, while practically offering recommendations for strengthening leadership practices, compensation fairness, and voluntary behaviors to enhance long-term operational readiness in military units.